Keyboard dynamics discrepancies between baseline and deceptive eyewitness narratives. Issue 1 (8th October 2020) - Tomas, Frédéric; Tsimperidis, Ioannis; Demarchi, Samuel; El Massioui, Farid
Summary: Information manipulation and cognitive load imposition make the production of deceptive narratives difficult. But little is known about the production of deception, and how its mechanisms may help distinguish truthful from deceitful narratives. This study focuses on the measurement of keystroke dynamics while typing truthful and deceptive eyewitness testimonies after a baseline assessment. While typing their narrative, some participants would undergo an auditory cognitive load. Results show that liars typed their story slower, and in less time than the truthful participants when compared to their respective baselines. The imposition of the auditory cognitive load showed adverse results, enhancing the amount of keystrokes and the time necessary to type the narrative. Classification shows better results for deceptive narrative when no auditory cognitive load is imposed. These results are discussed in terms of expanding current models to include the cognition of linguistic production and writing strategies.